2016
DOI: 10.14245/kjs.2016.13.3.124
|View full text |Cite
|
Sign up to set email alerts
|

The Factors That Affect Improvement of Neurogenic Bladder by Severe Lumbar Disc Herniation in Operation

Abstract: ObjectiveThis study analyzed retrospectively the bladder function of patients after early surgery for cauda equina syndrome (CES) performed within 24 or 48 hours, or after 48 hours of the onset of autonomic symptoms.MethodsWe retrospectively reviewed the clinical data of 31 patients after decompression surgery for lumbar disc herniation (LDH) who had been diagnosed with CES between January 2001 and December 2014 at Inha University Hospital. The following factors were assessed to evaluate the influence of time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
0
2
Order By: Relevance
“…This result was similar to that of some reports on CE syndrome. 26,27) In contrast, this study showed that the preoperative compression rate for intradural extramedullary Epi-CM located at the lower end of the spinal cord was negatively correlated with intraoperative BCR amplitude. Therefore, in patients with intradural extramedullary Epi-CM lesions with strong compression, it is considered that the BCR amplitude is likely to be reduced even with careful surgical manipulation.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This result was similar to that of some reports on CE syndrome. 26,27) In contrast, this study showed that the preoperative compression rate for intradural extramedullary Epi-CM located at the lower end of the spinal cord was negatively correlated with intraoperative BCR amplitude. Therefore, in patients with intradural extramedullary Epi-CM lesions with strong compression, it is considered that the BCR amplitude is likely to be reduced even with careful surgical manipulation.…”
Section: Discussioncontrasting
confidence: 73%
“… 26) In other reports of CE syndrome, no statistical relationship was observed between the degree of preoperative spinal canal compression and the prognosis of postoperative urinary symptom. 27) In this study, the preoperative compression rate was not correlated with the intraoperative BCR amplitude in the CE group with intradural extramedullary lesions. This result was similar to that of some reports on CE syndrome.…”
Section: Discussioncontrasting
confidence: 53%